The Ladybeetle Community (Coleoptera: Coccinellidae) in Southern Olive Agroecosystems of Spain - Cotes, B.; Campos, M.; Pascual, F.; Ruano, F. (ENVIRONMENTAL ENTOMOLOGY, 2010)
The aim of this survey is to faunistically describe ladybeetle assemblages from the canopies of olive orchards in southern Spain (Cordoba and Granada) and determine the indicator ladybeetle species that are representative of each region, taking into account (1) the ecological importance of predatory ladybeetle species in olive orchards and (2) the variability of ladybeetle community composition in relation to landscape configuration and different fanning systems (organic, integrated, and conventional), using ordination and classification methods. The total number of coccinellids collected was 481; they belonged to 9 genera and 13 species. Canonical correspondence analysis (CCA) showed a clear separation between orchards from Granada and orchards from Cordoba, taking into account ladybeetle species, environmental variables, and sampled orchards. The land use types and geographical locations showed that Scymnus mediterraneus lablokoff-Khnzorian 1972 and Platynaspis luteorubra (Goeze, 1777) captured at higher latitudes benefited more from a larger organic olive area and from the presence of holm oak forests in the surrounding area. Coccinella septempunctata L., 1758 and Hippodamia variegata (Goeze, 1777) were found at lower latitudes and at higher longitudes. Ladybeetle assemblages can vary in response to the type of farming system, especially with regard to pesticide use and landscape configuration. Nevertheless, evaluation of species composition might help identify the state of conservation of these agroecosystems. This knowledge could be used to improve the sustainability of agricultural landscapes to increase the presence of coccinellids and their ecological function in olive pest control.
The following values have no corresponding Zotero field: pub-location: 10001 DEREKWOOD LANE, STE 100, LANHAM, MD 20706-4876 USA publisher: ENTOMOLOGICAL SOC AMER
Keywords: Coccinellidae; Cordoba and Granada provinces

APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M.; Molinas, M. (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber